Bibliometric Analysis on EFL Publication Trends in 2011-2021 Using VOSviewer - Ikramunnisa, Erica; Mahardika, Surya; Afandi, Afandi; Rezeki, Yanti Sri (Celt: A Journal of Culture, English Language Teaching & Literature, 2022)
This study provides a comprehensive overview of current publication patterns in the field of English as a Foreign Language (EFL). In this research, the trends investigated are publication and citation growth, researcher’s productivity, and the most impactful publications. In addition to the publication trends, network visualizations of the terms co-occurrence and co-authorship are also presented in this research. A quantitative descriptive method with bibliometric analysis is employed as the research design of this research. The data analyzed are 6333 journal articles related to EFL published in 2011-2021. All of the data are obtained from the Scopus database. From the analysis using Scopus and Microsoft Excel, it was found that the highest publication growth in percent is in 2012 with a 98,6% of publication increase, and the highest publication growth in number is in 2020 with a total of 310 more publications compared to the previous year. Using the same tools, the researchers also found that the most productive author is Karim Sadeghi with 10 publications, and the most cited publication is an article titled 'English achievement and student motivation in CLIL and EFL settings' by David Lasagabaster. Meanwhile, from the network visualizations using VOSviewer, the researchers concluded that there are two major research themes in EFL, namely pedagogy and affective factors in learning, and the most collaborative author based on the co-authorship analysis is Ehsan Namaziandost.